Complex of GM1- and GD1a-like lipo-oligosaccharide mimics GM1b, inducing anti-GM1b antibodies. - Michiaki Koga; Michel Gilbert; Jianjun Li; Nobuhiro Yuki (PLoS ONE, 2015)
Molecular mimicry between Campylobacter jejuni lipo-oligosaccharides (LOSs) and human gangliosides GM1 and GD1a induces the production of anti-GM1 and anti-GD1a antibodies, and the development of Guillain-Barré syndrome. Complexes of two different gangliosides form new molecular shapes capable of enhancing recognition by anti-ganglioside antibodies. To test the hypothesis that the complex of GM1-like and GD1a-like LOSs of C. jejuni induces the development of anti-GM1b antibodies in Guillain-Barré syndrome patients.Mass spectrometry analysis determined the LOS outer core structures, with which mice were immunized. IgG antibodies to single gangliosides and complex of gangliosides were tested in sera from Guillain-Barré syndrome patients from whom C. jejuni LOS had been isolated.Two isolates from GBS patients who had anti-GM1b antibodies, but neither anti-GM1 nor -GD1a antibodies, expressed both GM1-like and GD1a-like LOSs, but not GM1b-like LOS. Anti-GM1b antibodies were induced in one of the mice immunized with the C. jejuni bearing GM1-like and GD1a-like LOS. Sera from 20 patients had antibodies to the complex of GM1 and GD1a, all of which carried anti-GM1b reactivity. Five of these sera harbored neither anti-GM1 nor anti-GD1a antibodies. IgG antibodies to the complex were absorbed by GM1b, but by neither GM1 nor GD1a.GM1-like and GD1a-like LOSs form a GM1b epitope, inducing the development of anti-GM1b antibodies in patients with Guillain-Barré syndrome subsequent to C. jejuni enteritis. Here, we present a new paradigm that the complex of two different structures forms a new molecular mimicry, inducing the production of autoantibodies.